2015
DOI: 10.1021/acs.jpca.5b04040
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Clustering of a Cyclohexene Autoxidation Product C6H8O7 with Itself and Sulfuric Acid

Abstract: We investigate the molecular interactions between sulfuric acid and a recently reported C6H8O7 ketodiperoxy acid formed through autoxidation from cyclohexene and ozone. Structurally similar but larger ELVOC (extremely low volatility organic compound) products formed from autoxidation of monoterpenes are believed to play a major role in the formation and early growth of atmospheric aerosol particles. Utilizing density functional theory geometries, with a DLPNO-CCSD(T)/def2-QZVPP single point energy correction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 38 publications
2
50
1
Order By: Relevance
“…from the -OOH group to the O=C). This internal hydrogen bond needs to be broken to form a new hydrogen bond with sulfuric acid 19 and causes the interaction of the peroxy acid to be significantly weaker (by 2.1 kcal/mol) than the individual contributions from an peroxide (-1.8 kcal/mol) and a carbonyl group (-1.7…”
Section: Interaction Between H 2 So 4 and Common Functional Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…from the -OOH group to the O=C). This internal hydrogen bond needs to be broken to form a new hydrogen bond with sulfuric acid 19 and causes the interaction of the peroxy acid to be significantly weaker (by 2.1 kcal/mol) than the individual contributions from an peroxide (-1.8 kcal/mol) and a carbonyl group (-1.7…”
Section: Interaction Between H 2 So 4 and Common Functional Groupsmentioning
confidence: 99%
“…Using the CCSD(T)-F12a/VDZ-F12 binding energy calculations of the organic acids ( Figure 1) as a benchmark set we assess the performance DLPNO-CCSD(T) using the cc-pVXZ (X= D,T,Q), aug-cc-pVXZ (X= D,T) and Def2-QZVPP basis sets as shown in Table S5 in the Supporting Information. The Def2-QZVPP basis set, which we have previously used in connection with the DLPNO method for studying the interaction between sulfuric acid and highly oxidized organic compounds, 19,20,71 We calculate the reaction free energy of sulfuric acid clustering with the common monoterpene markers: pinic acid, 72-76 3-methyl-1,2,3-butanetricarboxylic acid (MBTCA), 77,78 terebic acid, 79-81 3-hydroxy glutaric acid 79,82 and terpenylic acid. [79][80][81]83 The pinic acid and MBTCA cluster structures have been taken from previous studies.…”
Section: Clustering Of H 2 So 4 and Monoterpene Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] It has recently been suggested that low-volatile organic compounds participate in the first steps of new-particle formation, 10,11 but molecular-level explanation and details concerning the involvement of oxidized organic compounds are still missing. [12][13][14] Specifically, recent laboratory studies have indicated that ions can play a major role in organics-driven particle formation by enhancing the initial molecular cluster formation. 15 Volatile organic compounds (VOCs) are emitted into atmosphere from both anthropogenic and natural sources.…”
Section: -Introductionmentioning
confidence: 99%
“…) yields binding energies with lower stability than canonical coupled cluster methods, and therefore it can be used as a lower bound for the "true" cluster binding energies 12. As…”
mentioning
confidence: 99%